1971
DOI: 10.1029/jb076i017p03953
|View full text |Cite
|
Sign up to set email alerts
|

Microearthquakes, swarms, and the geothermal areas of Iceland

Abstract: More than 2100 microearthquakes were recorded and crudely located by using data from portable seismographs operated in Iceland during the summer of 1968. Another 600 events were located more precisely in three areas by using data from tripartite arrays. The earthquakes recorded are largely confined to 13 regions that are generally less than 100 km2 in area. Most of the well‐located events are at depths of 2 to 6 km but some less well located events may be as deep as 13 km. The microearthquakes are largely conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…1a): due to the westward American-Eurasian plate boundary migration, relative to the stable Icelandic hotspot, volcanic activity has progressively migrated eastward (Garcia et al, 2003;Ward and Björnsson, 1971;Saemundsson, 1974), from the West Volcanic Zones (N3 Myr; Garcia et al, 2003) towards the today active rifts of the North and the East Volcanic Zones, hosting the currently most active volcanic systems (Fig. 1a).…”
Section: The Natural Gas Datasetmentioning
confidence: 99%
“…1a): due to the westward American-Eurasian plate boundary migration, relative to the stable Icelandic hotspot, volcanic activity has progressively migrated eastward (Garcia et al, 2003;Ward and Björnsson, 1971;Saemundsson, 1974), from the West Volcanic Zones (N3 Myr; Garcia et al, 2003) towards the today active rifts of the North and the East Volcanic Zones, hosting the currently most active volcanic systems (Fig. 1a).…”
Section: The Natural Gas Datasetmentioning
confidence: 99%
“…The first experiment was conducted on Surtsey island produced in the eruption of 1963-1967 off the south coast (Einarsson, 1974). Microearthquake surveys were done of the whole country (Ward et al, 1969;Ward and Björnsson, 1971). Temporary seismic networks were operated on the Reykjanes Peninsula (Björnsson et al, in review) and prototype instruments were installed at permanent locations in South Iceland.…”
Section: Monitoring Systemsmentioning
confidence: 99%
“…Perhaps predictably, the recorded earthquake activity has similarly shown great variability. Research in Iceland by Ward et a3 (1969) and Ward and Bjornsson (1971) has shown that geothermal areas structurally related to a large number of faults and fissures are typified by high activity, whereas areas related to acidic intrusions or minor faulting contain only slight activity. These investigators have shown that the geothermal areas and the fissuring, faulting and seismicity are possible manifestations of transform faulting.…”
Section: Introductionmentioning
confidence: 99%
“…This apparent paradox may, in part, be an artifact of the current techniques that utilize the seismic data. In the above-mentioned study of earthquakes in Iceland (Ward and Bjornsson, 1971) the investigators concluded that the temporal distribution of earthquakes was not random. The statistical analysis was not extended further in order to answer the question: At what interoccurrence times did the distribution strongly deviate from random and where were those non-random events located?…”
Section: Introductionmentioning
confidence: 99%